Work stress, eating habits and anthropometric nutritional status in administrative and operational workers of a private clinic in Lima, 2018 - Manzano Huaracallo, Juan (2020)
Objective: To determine the relationship between work stress, eating habits and anthropometric nutritional status in administrative and operational workers of a private clinic in Lima. Methodology: Study of quantitative approach, cross-section, non-experimental design, and correlational descriptive type. A sample of 150 adult workers, divided into administrative and operational, Instruments: Was selected by intentional non-probabilistic sampling. Surveys of ILO labor stress and eating habits were applied, in addition to anthropometric nutritional evaluation. Results: Participants showed low levels of work stress, with 93.3% for operational workers and 94.7% for administrative workers; they also presented adequate eating habits in 72% and 66.7% respectively; Finally, 44% of operational workers were overweight, while 60% of administrative workers had a normal BMI. It was shown that for the administrative staff there is a statistically significant correlation between the variables (p <.05), but not for the operating group (p> .05). Conclusion: work stress and eating habits of administrative workers had an impact on their nutritional status, but not on operational workers, however, both groups had low levels of stress and adequate eating habits; Therefore, healthy work environments could have a positive impact on their health.